Differential expression profile of membrane proteins in L-02 cells exposed to trichloroethylene. (October 2016) - Hong, Wen-Xu; Huang, Aibo; Lin, Sheng; Yang, Xifei; Yang, Linqing; Zhou, Li; Huang, Haiyan; Wu, Desheng; Huang, Xinfeng; Xu, Hua; Liu, Jianjun
Trichloroethylene (TCE), a halogenated organic solvent widely used in industries, is known to cause severe hepatotoxicity. However, the mechanisms underlying TCE hepatotoxicity are still not well understood. It is predicted that membrane proteins are responsible for key biological functions, and recent studies have revealed that TCE exposure can induce abnormal levels of membrane proteins in body fluids and cultured cells. The aim of this study is to investigate the TCE-induced alterations of membrane proteins profiles in human hepatic L-02 liver cells. A comparative membrane proteomics analysis was performed in combination with two-dimensional fluorescence difference gel electrophoresis and matrix-assisted laser desorption/ionization time-of-flight tandem mass spectrometry. A total of 15 proteins were identified as differentially expressed (4 upregulated and 11 downregulated) between TCE-treated cells and normal controls. Among this, 14 of them are suggested as membrane-associated proteins by their transmembrane domain and/or subcellular location. Furthermore, the differential expression of β subunit of adenosine triphosphate synthase (ATP5B) and prolyl 4-hydroxylase, β polypeptide (P4HB) were verified by Western blot analysis in TCE-treated L-02 cells. Our work not only reveals the association between TCE exposure and altered expression of membrane proteins but also provides a novel strategy to discover membrane biomarkers and elucidate the potential mechanisms involving with membrane proteins response to chemical-induced toxic effect.